The role of R&D in new firm growth - Erik Stam; Karl Wennberg (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
Innovative start-ups are an important driver of economic growth. This article presents empirical evidence on the effects of R&D on new product development, inter-firm alliances and employment growth during the early life course of firms. We use a dataset that contains a sample of new firms that is representative for the whole population of start-ups. This dataset covers the first six years of the life course of firms. R&D reveals to play several roles during the early life course of high tech as well as high growth firms. The effect of initial R&D on high tech firm growth runs via increasing levels of inter-firm alliances in the first post-entry years. R&D efforts enable the exploitation of external knowledge. Initial R&D also stimulates new product development later on in the life course of high tech firms, but this does not seem to affect firm growth. R&D does not affect the growth rate of new low tech firms, which seems to be driven mainly by the growth ambitions of the founding entrepreneur. The results show that R&D matters for a limited but important set of new high tech and high growth firms, which are key in innovation and entrepreneurship policies.
Keywords: D21; L23; L25; L26; M13; 330; New Firms; Innovation; R&D; firm growth; alliances; product development; Unternehmensgründung; Innovation; Industrielle Forschung; Unternehmenswachstum; Forschungskooperation; Unternehmensentwicklung; Niederlande